Hubungan IMT, kekuatan, daya ledak, kelincahan, dan daya tahan kardiovaskuler dengan kemampuan dribbling bola basket - Jati, Jati Laksono; Siti Nurrochmah; AFRIAN HERMAWAN; MUHAMMAD JUFRI; GOD LIFE ENDOB M M (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Sports are considered physical activities undertaken primarily to enhance basic body movement skills or specific sports abilities. Basketball has become one of the most popular and widely enjoyed sports among the general public. As sports disciplines evolve, optimal efforts are required to achieve maximum performance. However, achieving peak performance in sports is not as easy as it might seem. This research aims to further explore the correlational relationship between body mass index, arm muscle strength, arm muscle power, agility, and cardiovascular endurance to support the dribbling abilities of extracurricular participants at SMAN 1. Data was collected through observation and analyzed using correlational regression statistical approaches, detailing a population of 35 participants, with a sample size of 35 participants. The research findings indicate a significant relationship between body mass index, arm muscle strength, arm muscle power, agility, cardiovascular endurance, and the dribbling abilities of the participants